Eco Sustainable Rail - Valorization of Mixed Plastics in the Development of Eco-Sustainable Railways - Carvalho, Joana; Mota, André; Ribeiro, André; Soares, Margarida; Araújo, Jorge; Vilarinho, Cândida (European Journal of Sustainable Development, 2018)
The mixed plastics, by their heterogeneity and contamination characteristics, constitute the extreme situation of difficulty in recycling, which has greatly contributed to a high fraction of mixed plastics landfilled. This situation is a cause for concern, and it is imperative to search for new application solutions for these wastes and its valorization as a raw material of high value-added products. Currently exists in Portugal and globally a need to find solutions for railway sleepers, to be a viable alternative to the replacement of wood railway sleepers, which usually have a special application and cannot be replaced by cement solutions existing on the market. Thus, the ECO SUSTAINABLE RAIL project intends to meet the listed requirements, through the mixed plastics valorization in the development of the eco-sustainable sleepers, mostly made of mixed plastics, to be tested in real scenario of operation in Infrastructures of Portugal. The ECO SUSTAINABLE RAIL project will be supported in the development of three research lines (research and development of a new material mostly of mixed plastics, research of a sleeper geometry, research of a new production process), the development of life-cycle analysis and environmental assessment of the sleepers real scenario and the sleepers testing in real operating condition. For the project execution, it was established a set of entities consortium, with experience and complementary skills, including the leading EXTRUPLÁS company, the Innovation Pole in Polymer Engineering (PIEP) and the Centre for Waste Valorization (CVR), that with the technical support of Infrastructures of Portugal (IP) will be able to develop and test a new railway sleeper of quality and with less environmental impact. Overall the project ECO SUSTAINABLE RAIL will contribute to reduce the deposition of mixed plastic in landfills, to respond to a need of the railway sector, and to allow the expansion and differentiation of the EXTRUPLÁS products portfolio, which will strengthen its position in the plastic recycling sector. Keywords: Mixed plastics, Valorization, Eco-sustainable railways